2008
DOI: 10.1097/ta.0b013e318163359d
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety in Trauma: Maximal Impact Management Errors at a Level I Trauma Center

Abstract: Management errors in the basics of trauma care continue even in established trauma centers, despite guidelines, protocols, and continuous performance improvement. Standardized reporting such as the taxonomy may result in progressive collection of patient safety data and lead to innovations to minimize these errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 17 publications
3
46
1
1
Order By: Relevance
“…[2][3][4][5][7][8][9]11,12,[14][15][16][17]21,22,[24][25][26][28][29][30][31][32][34][35][36][37][38][39] Most articles were published in English-speaking countries, especially in the United States (51.7%), England (17.2%), and Australia (13.8%). They were mostly published in English (96.6%) and the largest number of authors in a study was 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][7][8][9]11,12,[14][15][16][17]21,22,[24][25][26][28][29][30][31][32][34][35][36][37][38][39] Most articles were published in English-speaking countries, especially in the United States (51.7%), England (17.2%), and Australia (13.8%). They were mostly published in English (96.6%) and the largest number of authors in a study was 12.…”
Section: Resultsmentioning
confidence: 99%
“…20 Age restrictions were applied in nine studies: adolescents 7 or adults only. 2,3,9,12,14,24,26,35 The upper age limit for defi ning avoidable trauma deaths was not described in the studies reviewed and can be a limitation since the aging process may affect an individual's response to treatment. Recent studies that have classifi ed deaths from other diseases take the age of 75 as the upper limit of avoidability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also showed that human errors are frequently predominant at surgery centers and Emergency Departments (22) . The major failures observed in the SC were: inadequate surgical resuscitation, delay in bleeding control, and failure to identify injuries (5,22) .…”
Section: Rev Esc Enfermmentioning
confidence: 89%
“…When the literature was reviewed for medical errors related to traumatc deaths, it was seen that medical errors were categorised in different ways. In a study by Ivatury et al [19] evaluating seven hundred and sixty-four cases of traumatic deaths, medical errors have been reported at a rate of 9.9%. Zafarghandi et al [20] have evaluated one hundred and sixty-five traumatic deaths in Tehran and classified the cases as with and without central nervous system involvement, and medical errors have been categorised as diagnostic errors and teatment errors.…”
Section: Medical Errorsmentioning
confidence: 99%